(untitled) (Scientific journal of the Fergana State University, 2025)
The article explores the theoretical foundations for studying the dialectical relationship between moral and religious values in the era of globalization. It provides a dialectical analysis of the interactions between these values during globalization and examines the problems and solutions regarding their future relations. Additionally, the dialectical relationships and development of moral and religious values in New Uzbekistan are analyzed.